2015
DOI: 10.1002/job.2020
|View full text |Cite
|
Sign up to set email alerts
|

Emotional labor threatens decent work: A proposal to eradicate emotional display rules

Abstract: Emotional labor-the management of emotional displays as part of one's work role-has emerged as a growth area of study within organizational behavior and customer service research. In this article, we call attention to the human costs of "service with a smile" requirements with little benefits. We first review the evidence showing that requiring positive emotions from employees induces dissonance and depleted resources, which hinders task performance and threatens well-being. We articulate how formalized emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 100 publications
(132 reference statements)
8
144
1
1
Order By: Relevance
“…"Emotional Labor" rules commanding displays of positive emotions are disrespectful to employees and to customers (Grandey et al 2015). Most importantly, service research needs to develop tools for effective identification and reaction to customer needs and emotions (cf.…”
Section: )mentioning
confidence: 99%
“…"Emotional Labor" rules commanding displays of positive emotions are disrespectful to employees and to customers (Grandey et al 2015). Most importantly, service research needs to develop tools for effective identification and reaction to customer needs and emotions (cf.…”
Section: )mentioning
confidence: 99%
“…Recent meta-analyses have shown that, depending on the strategy workers use to regulate their emotions during the service, deep or surface, the consequences for service performance and health will be different (Hülsheger & Schewe, 2011;Mesmer-Magnus, DeChurch, & Wax, 2012;Wang, Seibert, & Boles, 2011). Using a deep acting strategy leads to better performance and does not harm workers' wellbeing, but using a surface acting strategy often has negative consequences for workers' personal wellbeing (Grandey, Rupp, & Brice, 2015;Hülsheger, Lang, & Maier, 2011). However, personal differences such as beliefs and skills may buffer or intensify these relationships (Gracia & Ashkanasy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further to this, any prediction or advice in relation to the exact outcomes of worker emancipation from emotional repression would seem to be diametrically opposed to the frequently invoked notion within critical theory of workers having the potential and need for creative, spontaneous and autonomous action (Alvesson and Willmott, 1992;Grandey et al, 2015). Instead, I advocate the position that the effects of emotion research more generally, and its effects in the context of this book, often do not immediately manifest themselves.…”
Section: How 'Normative' Is Appliedmentioning
confidence: 86%
“…In addition to the cabbage example stated earlier, it has been known for some time that employees' displays of 'friendly demeanours' are related to job descriptions and consequent rewards (i.e., wages). However, it is well documented that engaging in emotional labour (Hochschild, 1983), which requires workers to regulate their emotions according to the display rules imposed by organizations, can have detrimental consequences for them, such as the experience of burn-out and exhaustion (Grandey et al, 2015;Hülsheger and Schewe, 2011). However, a more recent and more ominous development is that failure to display such friendly demeanours entails that the entire shift in a fast-food restaurant might lose out on its bonus (as opposed to a single worker being reprimanded by management for failing to be 'happy' at work).…”
Section: Theoretical and Practical Relevancementioning
confidence: 99%
See 1 more Smart Citation